(Ph3P)4C4P4: Effect of substitution on the Oligomerization of carbon phosphide radicals - Dr. Moritz Scharnhölz; Dr. Jose Juan Gamboa Carballo; Dr. Nils Trapp; Dr. Rene Verel; Dr. Peter Coburger; Prof. Dr. Hansjörg Grützmacher (ChemistryEurope)
Abstract Dehalogenation of (PBr)2C2(PPh3)2 with potassium graphite, KC8, leads to Cs‐P4C4(PPh3)4, which can be viewed as a PPh3 adduct of a Cs‐symmetric P4C4 cage. An isolable intermediate was found and in combination with DFT calculations, the structure of a S4‐symmetric P4C4(PPh3)4 cage is proposed for this species. That a 1,3‐diphosphete type Ph3P→P2C2←PPh3 heterocycle is a short‐lived intermediate in the dehalogenation reaction is indicated by trapping experiments which allowed to isolate and fully characterize the [Fe(CO)4] complexes [Fe(CO)4(κ‐P−P2C2{PPh3}2] and [(Fe(CO)4)2(μ2‐κ‐P−P2C2{PPh3}2]. The conversion of S4‐P4C4(PPh3)4 to Cs‐P4C4(PPh3)4 prompted a (re)investigation of the isomerization of various P4X4 species (X=S, NH, NMe; CH2), which shows that these proceed on Minimum Energy Reaction Pathways (MERPs) with two transition states embracing one intermediate. In contrast, the isomerization S4‐P4C4(PR3)4 to Cs‐P4C4(PR3)4 is a one‐step process.